Industry-Specific Human Capital: Evidence from Displaced Workers - Neal, Derek (Journal of Labor Economics, 1995)
Results from the Displaced Worker Surveys show that the wage cost of switching industries following displacement is strongly correlated with predisplacement measures of both work experience and tenure. Workers apparently receive compensation for some skills that are neither completely general nor firm-specific but rather specific to their industry or line of work. Further, among displaced workers who find new jobs in their predisplacement industry, postdisplacement returns to predisplacement job tenure resemble cross-section estimates of the returns to current seniority. This suggests that firm-specific factors may contribute little to the observed slope of wage-tenure profiles. Copyright 1995 by University of Chicago Press.